PENGEMBANGAN KEAGAMAAN ANAK USIA DINI - Khadijah Khadijah (JURNAL RAUDHAH, 2016)
Religious early childhood that everything related or associated withattitudes, rituals and beliefs of children who are religious. Religiousdevelopment in children starts from the fairly tale stage and The realisticstage. As for religious properties owned subsidiary that is unreflective,egocentric, anthromorphis, verbalis and ritualists, imitative and awe /admiration. Religious values in children can be developed through theexample, habituation, advice, stories, songs and gift-giving. While theconstraints faced by parents/educators in internalize religious values are:1) parents/educators are less able to provide good role model, 2) theneighborhoods where children live less support or do not have consistencyin habituation, 3) lack of control storytelling techniques, and 4) parents /educators more berkomentator on children's negative behavior, and oftenignore the positive behavior of children.Kata Kunci:Pengembangan, Keagamaan, Anak Usia Dini.